2020
DOI: 10.1111/jog.14449
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine transplantation of autologous menstrual blood stem cells increases endometrial thickness and pregnancy potential in patients with refractory intrauterine adhesion

Abstract: Aim: This study was designed to evaluate the effects of intrauterine transplantation of menstrual blood stem cells (MenSCs) on endometrial thickness and pregnancy outcomes in patients with refractory intrauterine adhesion (IUA). Methods: This study included a group of infertile women (n = 12, age 22-40 years), with refractory IUA. Autologous MenSCs isolated from the women's menstrual blood were expanded in vitro and transplanted into their uteruses, followed by hormone replacement therapy. Transvaginal ultraso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…by MenSCs transplantation, and some of them achieved clinical pregnancy (9). In that study, five out of 12 patients got pregnant, and in other words, there was a pregnancy rate of 41.7% (9).…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…by MenSCs transplantation, and some of them achieved clinical pregnancy (9). In that study, five out of 12 patients got pregnant, and in other words, there was a pregnancy rate of 41.7% (9).…”
Section: Introductionmentioning
confidence: 72%
“…Autologous MenSCs have been transplanted to patients with refractory IUA for clinical therapy. The results revealed that patients with refractory IUA had thicker endometrium and prolonged menstrual duration managed by MenSCs transplantation, and some of them achieved clinical pregnancy ( 9 ). In that study, five out of 12 patients got pregnant, and in other words, there was a pregnancy rate of 41.7% ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Salama et al [86] found that BM-MSCs up-regulated the expression of PCNA and VEGF, down-regulated the expression of NF-κB and effectively repaired the injured endometrium in the rat IUA model. Ma et al [87] reported that Men-SCs transplantation could promote endometrial repair in patients with refractory IUA, which showed increased endometrial thickness, prolonged menstrual duration, and increased pregnancy rate. In a current clinical study, patients with unresponsive thin endometrium caused by IUA received UC-MSCs therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, more importance was attached to biotherapy, especially in the field of stem cell therapy. Bone marrow mesenchymal stem cells (BMSCs) [59], umbilical cord mesenchymal stem cells (UCMSCs) [60], and menstrual blood mesenchymal stem cells (MbMSCs) [61,62] have been used clinically in patients with IUA, resulting in an improvement in reproductive outcome. Furthermore, researchers reported that stem cells could not only promote endometrial cell proliferation, but also inhibit the process of fibrosis [63].…”
Section: Discussionmentioning
confidence: 99%